The Role of Long Non-Coding RNAs in Thyroid Cancer - Peng, Xuejiao; Zhang, Kun; Ma, Li; Xu, Junfeng; Chang, Weiqin (Frontiers in Oncology, 2020)
Thyroid cancer, the most common endocrine malignancy, has become the most commonly diagnosed malignant solid tumor. Moreover, some cases have poor prognosis, and the survival period is only 3–5 months. Long noncoding RNAs (lncRNAs) are a group of functional RNA molecules more than 200 nucleotides in length that lack the ability to encode protein but participate in all aspects of gene regulation. Functionally, many lncRNAs play essential roles in epigenetic regulation at transcriptional and post-transcriptional levels via various molecular mechanisms. Recent studies have discovered important roles for lncRNAs during the complex process of carcinogenesis in thyroid cancer. In this review, we focus on lncRNAs dysregulated in thyroid cancer and summarize recently reported associations between lncRNAs and thyroid cancer in order to demonstrate the significant value of lncRNAs in diagnosis and treatment.